Determinants of Financial Management Behavior of MSMEs: The Mediating Role of Financial Self-Efficacy - Kamellia, Siti; Tubastuvi, Naelati (Universitas Muhammadiyah Pontianak, 2025)
Financial management is key for business actors in achieving business financial efficiency and optimization. This study aims to investigate the impact of financial literacy, financial inclusion, and locus of control on the financial management behavior of MSMEs in Purwokerto, Indonesia, with financial self-efficacy serving as the mediating variable. A quantitative approach was applied in this study, involving 211 purposively selected MSME respondents. Data analysis was conducted using SmartPLS 4, which involved testing both the outer model and the inner model. The findings suggest that financial literacy does not have a significant impact on financial self-efficacy. In contrast, financial inclusion has a negative impact, while locus of control has a positive effect on financial self-efficacy. The results also indicate that financial literacy and financial inclusion have a positive impact on financial management behavior. In contrast, locus of control and financial self-efficacy do not exhibit a significant effect. In addition, financial self-efficacy is not able to mediate the factors that influence financial management behavior. Thus, the results show that improving financial management behavior can be achieved through optimizing financial literacy and financial inclusion.